KETENTUAN PEMENUHAN HAK ANAK LUAR KAWIN ATAS PENERIMAAN HARTA WARISAN DITINJAU DARI KITAB UNDANG-UNDANG HUKUM PERDATA (STUDI KASUS: PUTUSAN MAHKAMAH AGUNG NOMOR 1594K/PDT/2018) - Vanessa Vanessa; Gunawan Djajaputra (Faculty of Law - Tarumanagara University, 2022)
Regarding the legal position of illegitimate child in terms of inheritance which is different from legitimate child, it quite often found errors occur. The incident where an error occurred in the distribution of inheritance was also found in the case of the Supreme Court's Decision Number: 1594K/Pdt/2018. Based on this case, a problem arises regarding the equal distribution of inheritance between legitimate child and illegitimate child. Then, problems arise, namely how the legal position of illegitimate children in receiving inheritance and what form of legal protection for illegitimate children who do not fulfil Article 272 of the Civil Code in receiving inheritance. The author uses normative legal research methods. the legal position of an illegitimate child who fulfills Article 272 of the Civil Code with a legitimate child is only the same for the ownership of saisine, heriditatis petitio, and legitieme portie rights, but the share of inheritance is different. Meanwhile, illegitimate children who do not fulfil Article 272 of the Civil Code can obtain legal protection like receiving grants or testaments. So, the author can conclude that the portion of illegitimate children who fulfill Article 272 of the Civil Code gets a smaller share than legitimate children. For illegitimate children who do not fulfil Article 272 of the Civil Code, they are still entitled to legal protection like receiving grants or testaments. It is better for people who will become heirs to be able to distribute inheritance to their heirs fairly and equitably based on the provisions stipulated in the Civil Code.